PERANAN CSR DALAM MEMEDIASI PENGARUH DIGITALISASI, KEPUTUSAN INVESTASI DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN (Studi Pada Perusahaan Farmasi di BEI Periode 2016-2020) - Hari Purnama (Medikonis, 2022)
ABSTRACT This study aims to examine the effect of digitization, investment decisions and financial performance on firm value. To examine the effect of digitization and investment decisions on financial performance. To examine the effect of Digitalization and Investment Decisions on Corporate Value moderated by CSR. The variables of this study consisted of independent, dependent and mediating variables. The independent variables of this study are digitalization, investment decisions and financial performance, the dependent variable is firm value and the moderating variable is CSR. The population in this study are all pharmaceutical companies on the Indonesia Stock Exchange for the 2016-2020 period. Sampling technique purposive sampling. Methods of data collection using literature and documentation. The analytical technique used is path analysis or path analysis using multiple linear regression with a significance level of 5%. The results of research on digitization, financial performance and CSR have a positive and significant effect on firm value. While the Investment Decision does not affect the Company Value. Digitalization, and Financial Performance have a positive and significant impact on CSR. Meanwhile, investment decisions have no effect on CSR. CSR is able to mediate the relationship between the influence of digitalization, investment decisions and financial performance on firm value. Keywords: Digitalization, Investment Decision, Financial Performance, CSR and Company Value